Improvement of Plastic Waste Processing In The Plastic Waste Processing Industry at Tanjungsari District Sumedang - Ahmad Munandar; Ketut Abimanyu Munastha; Nurwathi Nurwathi; Udin Komarudin; Leni Herdiani; R. Ismet Ruhimat (Institut Teknologi Nasional, Bandung, 2020)
The waste problem is a very complex discussion. Every day thousands of tons of waste are produced by industry and households. The most complicated problem of handling waste today is plastic. Until now, Indonesia is the number two plastic waste-producing country in the world, amounting to 187.2 million tons/year (2015). This problem needs to be solved scientifically, given the pollution generated by plastic waste is getting worse. One of the efforts made is to recycle plastic waste, such as the people of Cinanjung Village, Kutawaringin Village, and Hegarmanah Village, Tanjungsari District, Sumedang Regency. The problems that arise are (1) the process of making